Beyond courage : the untold story of Jewish resistance during the Holocaust - Rappaport, Doreen (Candlewick Press, 2012)
"Through twenty-one meticulously researched accounts-- some chronicled in book form for the first time-- Doreen Rappaport illuminates the defiance of tens of thousands of Jews across eleven Nazi-occupied countries during World War II."--Amazon.com.